Psychology - Ciccarelli, Saundra K. (Pearson Prentice Hall, 2006)
Using the APA undergraduate psychology learning outcomes, the author establishes clear learning objectives for readers and ties the text assessment to these objectives. Praised for a very engaging writing style, comprehensive coverage of key research, and strong pedagogical features, Ciccarelli focuses on getting students to actually read theirnbsp;textbook. Student feedback from numerous class tests and instructor feedback from an extensive reviewing process emphasize the appeal of Ciccarelli's approach to teaching and learning in today's classroom.nbsp;nbsp; nbsp;